Peningkatan Hasil Belajar Siswa Kelas VI melalui Metode Pembelajaran Decision Making dengan Puzzle Peta Sumatera di SDN 59 Pangkalpinang - Sjaipul Kori; M Iqbal Arrosyad; Gatot Afrianto (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
This study aimed to improve the learning outcomes of sixth-grade students at SD Negeri 59 Pangkalpinang by implementing the Decision Making learning method using map puzzles of Sumatera. The research employed a Classroom Action Research (CAR) methodology, conducted in two cycles, each consisting of two sessions. In the first cycle, the application of this method resulted in a classical completeness rate of 71%, indicating a need for improvement. However, after applying the method in the second cycle, a significant increase was observed, with the completeness rate reaching 87%. Data were collected through learning outcome tests and analyzed descriptively to assess the effectiveness of the method and media used. The findings demonstrate that the Decision Making method, when combined with map puzzles, effectively enhances student learning outcomes, showing notable improvement from the first to the second cycle. This study suggests the use of similar methods in different contexts to further evaluate their success and effectiveness.